Feeding Behavior of Etawa Crossbred Dairy Goats in Consuming Cnidoscollus aconitifolius as a Substitute Feed and Its Correlation with Palatability and Body Weight Gain - Putri, Aprillia Ika; marjuki, Marjuki; Hartutik, Hartutik; subagyo, Ifar; Mashudi, Mashudi; Huda, Asri Nurul; Hadin Husnassabil, Ahmad (CV. Komunitas Dunia Peternakan, 2026)
This study evaluated the feeding behavior and palatability of Etawa Crossbred (PE) dairy goats fed diets with partial substitution of Cnidoscolus aconitifolius forage. An in vivo field experiment was conducted using a Completely Randomized Design with four dietary treatments and three replications. The treatments consisted of: (T0) Leucaena leucocephala (lamtoro) as the basal forage; (T1) lamtoro supplemented with concentrate; (T2) lamtoro plus concentrate with 10% substitution of lamtoro dry matter by C. aconitifolius; and (T3) lamtoro plus concentrate with 20% substitution of lamtoro dry matter by C. aconitifolius. Parameters observed included feed intake (dry matter, organic matter, crude protein, and crude fiber), body weight change, and feeding behavior related to forage preference. The goats consistently consumed forage prior to concentrate and exhibited a higher preference for diets containing C. aconitifolius. Inclusion of C. aconitifolius reduced lamtoro intake; however, no significant differences were observed among treatments for dry matter, organic matter, crude protein, or crude fiber intake (P>0.05). Body weight change showed a positive tendency in goats receiving 10% and 20% C. aconitifolius substitution, while goats fed the control diet experienced slight weight loss, although these differences were not statistically significant (P>0.05). In conclusion, C. aconitifolius demonstrated good palatability and potential as an alternative forage for PE goats when used as a partial substitute for lamtoro. Nevertheless, its inclusion at the tested levels did not significantly affect nutrient intake or body weight change. Further studies are recommended to optimize inclusion levels and feeding strategies to enhance its practical application in small ruminant production systems.